Estrategia de marketing en la Escuela Particular Luz Y Vida del cantón Babahoyo. - Tigrero Bricio, Jonathan Daniel (2023)
n a context of increasing competition and constant changes in the education market, the Private School “Luz y Vida” in the Babahoyo Canton recognizes the need to develop an effective marketing strategy to maintain its relevance and attract students, parents, and the community. The purpose of the research is to explore and design an appropriate marketing strategy for the school, involving a comprehensive analysis of various aspects affecting the institution. Several challenges were identified, including a lack of differentiation, limited community awareness, a constrained budget, intense competition, seasonal fluctuations, inadequate online presence, low student retention, ineffective communication, minimal community engagement, and the need to adapt to changing educational trends. To address these challenges, qualitative and quantitative approaches will be employed in the research. Qualitative methodology involves in-depth interviews with the school's administrative staff, while quantitative methodology includes structured surveys of parents of students. Survey results show that the majority of respondents perceive that the school offers unique educational programs, but there is a division regarding whether the school is well-informed about the community's needs. Furthermore, a significant portion of respondents perceives that the school faces budgetary limitations in its activities.